The authority of Scripture in Reformed theology : truth and trust - Belt, H. van den, 1971- (Studies in Reformed Theology, 2008)
The authority of Scripture is the cornerstone of Reformed theology. Calvin introduced the term autopistos from Greek philosophy to express that this authority does not depend on the church or on rational arguments, but is self-convincing. After dealing with Calvin's Institutes, the development of Reformed orthodoxy, and the positions of Benjamin B. Warfield and Herman Bavinck, the author draws theological conclusions, advocating a renewed emphasis on the autopistia of Scripture as starting point for Reformed theology in a postmodern context. The subject-object scheme leads to separating the certainty of faith from the authority of Scripture. The autopistia of Scripture, understood as a confessional statement, implies that truth and trust are inseparable.